Textbook outcome, chemotherapy compliance, and prognosis after radical gastrectomy for gastric cancer: A large sample analysis. Issue 10 (October 2022) - Chen, Jun-Yu; Lin, Guang-Tan; Chen, Qi-Yue; Zhong, Qing; Liu, Zhi-Yu; Que, Si-Jin; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; et al.
Abstract: Background: This study aims to analyze the effect of textbook outcome (TO) on the long-term prognosis and adjuvant chemotherapy (AC) compliance of patients with gastric cancer (GC) in a single institute. Materials and methods: Consecutive patients who underwent radical gastrectomy with pathological stage I-III at Union Hospital of Fujian Medical University from January 2010 to June 2017 were included. TO was defined as receiving a complete-potentially curative status, ≥15 lymph nodes examined, hospital stay ≤21 days, and freedom from intraoperative and postoperative complications, re-intervention in 30 days, 30-day readmission to the hospital or intensive care unit, and 30-day postoperative mortality. Results: Totally 3993 patients were included, of which 3361 (84.2%) patients achieved TO. The overall, disease-specific, and recurrence-free survival of patients achieving TO were significantly better than those of patients without achieving TO (all P < 0.05). The total number of AC cycles was greater and the interval from surgery to first AC was shorter in the TO group compared with the Non-TO group. Age >65 years old, open surgery, pT3-4 stage, and total radical gastrectomy (TG) were identified as related high-risk factors for failure to achieve TO. Laparoscopic surgery facilitated TO achievement in high-risk groups. Conclusion: TO is a reliable indicator of favorable prognosis of patients with GC and contributes to postoperative chemotherapy compliance. Age ≤65 years old, non-TG, pT1-2 stage, and laparoscopic surgery may promote the achievement of TO.